Eksperimen Pembelajaran Matematika Dengan Strategi Problem Based Learning (Pbl) Dan Discovery Learning (Dl) Terhadap Hasil Belajar Ditinjau Dari Keaktifan Belajar Siswa Kelas Vii Semester Gasal Smp Negeri 23 Surakarta Tahun Ajaran 2016/2017 - Widyawati, Rires; , Drs. Ariyanto, M.Pd (2017)
On this research has three purposes. (1) Analyze and examine the differences learning outcomes in terms of mathematics learning with strategies Problem Based Learning and Discovery Learning, (2) Analyze and examine the differences learning outcomes in terms of student's learning activeness, (3) Analyze and examine interaction strategies and student's learning activeness toward learning outcomes. This research quantitative type is quasi-experimental design. The population in this research there are seven classes of odd semester grade VII SMP Negeri 23 Surakarta on academic year 2016/2017. Sample consisted of two classes, experiment class treated PBL and control class treated DL. Technique use cluster random sampling. Methods of data collection used test, questionnaire and documentation. Techniques of analyzed use analysis of variance two path different cell. Before the test analysis is start, the sample must be tested prerequisites, the balance test, test normality and homogeneity test. The research with α = 5% result show that (1) there are differences learning outcomes in terms of mathematics learning with strategies Problem Based Learning and Discovery Learning, (2) there are differences learning outcomes in terms of student's learning activeness, (3) there is no interaction strategies and student's learning activeness toward learning outcomes. Keywords: discovery learning, learning outcomes, problem based learning, student's learning activeness